Curricular diversification and the validity of interculturality in the teachers of the Unidad de Gestión Educativa Local of Collao-Ilave - Pérez, Katia (2019)
The research was carried out with the purpose of determining the relationship between curricular diversification and the validity of interculturality in the teachers of the UGEL Collao - Ilave, regarding the variables: curricular diversification and the validity of interculturality. Methodologically, the research is descriptive correlational type; the population is made up of 50 teachers, who were given a survey of 20 items to measure the curricular diversification variable and a questionnaire was used to measure the validity variable of interculturality. To establish the correlation between the variables of curricular diversification and the validity of interculturality, the Pearson R coefficient was used. The results of the research are the following: There is a moderate positive correlation between curricular diversification and the validity of interculturality. This conclusion is based on Pearson's statistical correlation test of R that is equal to 0.408 **; which means that the existence of a curricular diversification will have a validity of moderate interculturality; the teachers of the UGEL Ilave consider interculturality valid.